Corpus Hermeticum - Hermes Trismegistus; Broek, R. van den 1931-; Quispel, G. 1916-2006; Ritman, Joost 1941- (Amsterdam In de Pelikaan, 1991)
The Corpus Hermeticum is a collection of 17 Koine Greek pseudepigraphical writings whose authorship is traditionally attributed to the legendary Hellenistic figure Hermes Trismegistus ("Thrice Great"), a syncretic combination of the Greek god Hermes and the Egyptian god Thoth. The treatises were originally written between c. 100 and c. 300 CE, but the collection as known today was first compiled by Medieval Byzantine editors, and translated into Latin in the 15th century by the Italian humanist scholars Marsilio Ficino (1433–1499) and Lodovico Lazzarelli (1447–1500).
I. Poimandres -- II. Een algemeen gesprek van Hermes met Asclepius -- III. Een gewijde verhandeling van Hermes -- IV. Het Mengvat of De Eenheid -- V. God: onzichtbaar en toch goed zichtbaar -- VI. Het Goede is alleen in God en nergens anders -- VII. Onwetendheid aangaande God: het grootste kwaad onder de mensen -- VIII. Van wat bestaat, vergaat niets -- IX. Inzicht en waarneming -- X. Openbaring van de driewerf grote Hermes: Sleutel -- XI. De Geest spreekt tot Hermes -- XII. De Geest die het Al doordringt: gesprek van de driewerf grote Hermes met Tat -- XIII. De driewerf grote Hermes spreekt tot zijn zoon Tat -- XIV. Het wezen van het Al -- XVI. Aforismen -- XVII. Beelden -- XVIII. Lofrede op het koningschap
Originally published in 1990
Keywords: Classical Antiquity (8th Century BC-6th Century AD); Philosophy; Hermeticism; Esotericism; Religion; Alexandria (Egypt)